Discovering Pluto : Exploration at the Edge of the Solar System - Cruikshank, Dale P.; Sheehan, William, 1954- (Book collections on Project MUSE., 2018)
The story of Pluto and its largest moon, from discovery through the New Horizons flyby--Provided by publisher.